REALIZATION OF SPEECH FUNCTION IN CIGARETTE’S SLOGANS - Ulan Tri Lestari; Rahmah Rahmah (LINGUISTICA, 2014)
ABSTRACT This study deals with realization of speech function in cigarette’s slogans. The objectives of the study were to identify the types of speech function realized in cigarette’s slogans, to identify the types of mood realized in cigarette’s slogans, and to find the most dominant type of speech function and mood in cigarette’s slogans. The data were cigarette’s slogans which were taken from advertising media like television, internet or billboard. There were found 38 slogans which consist of Speech Functions. Based on the analysis, there were only three speech functions found in the slogans. They were statement, question and command. The most dominant speech function used was statement. There were three moods found, they were declarative, interrogative and imperative. The most dominant type of mood was declarative.   Key words : speech function, mood, slogan